Artistas y metodologías en danza: una aproximación al estudio de la escenografía española de entreguerras - Murga Castro, Idoia (Anales de Historia del Arte, 2010)
The set and costume design for dance performance was a usual work among the Spanish painters in the 20th century, who considered the scene as an interesting space for experimentation with the new artistic languages and as a platform to widely spread their novelties. The contact between plastic arts and the other disciplines, movement, music, and literature, determines a complex analysis from different points of view. Starting with the most important artists and works of that time as a basic ground, this article presents various approaches to the study of the contemporary artist production in order to introduce new lines to the discussion on methodological questions and to enrich the exchange with other humanistic fields.
Keywords: Scenography; Costume design; Dance; Between the wars; 20th century art; Methods